Transformations of memory and the urban landscape of ancient Rome: some possibilities of long-term interpretation - Pires, Thiago de Almeida L. C. (Romanitas - Revista de Estudos Grecolatinos, 2018)
Review of: MORCILLO, M. G.; RICHARDSON, J. H.; SANTANGELO, F. (Ed.). Ruin or renewal? Places and the transformation of memory in the city of Rome. Roma: Quasar, 2016. 304 p.
Keywords: Transformation; Memory; Urban landscape; Ancient Rome